2019
DOI: 10.5114/hm.2019.83990
|View full text |Cite
|
Sign up to set email alerts
|

The report and analysis of the 2nd U21 European Deaf Football Championship, Stockholm, Sweden 2018

Abstract: Purpose. Almost no studies have documented or analysed sporting events for deaf players at the elite level. the aim of the study was to report on the 2 nd U21 European Deaf Football championship, analyse selected offensive actions and compare them with the 1 st European Deaf sports Organization (EDsO) U21 championship and Union of European Football Associations (UEFA) U21 events (2015 and 2017), as well as create a ranking of finalists of the deaf U21 tournaments. Methods. counting analyses were performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Some times for Paralympics competitors. A review of databases of scientific journals has identified only several publications concerning hard-of-hearing players and teams (Milašius et al, 2014;Palmer et al, 2006;Steward et al, 1991;Szulc, 2017Szulc, , 2019Szulc et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some times for Paralympics competitors. A review of databases of scientific journals has identified only several publications concerning hard-of-hearing players and teams (Milašius et al, 2014;Palmer et al, 2006;Steward et al, 1991;Szulc, 2017Szulc, , 2019Szulc et al, 2017).…”
Section: Introductionmentioning
confidence: 99%